Dependence maximization localization: a novel approach to 2D street-map-based robot localization. (16th November 2016) - Irie, Kiyoshi; Sugiyama, Masashi; Tomono, Masahiro
Abstract : Recently, localization methods based on detailed maps constructed using simultaneous localization and mapping have been widely used for mobile robot navigation. However, the cost of building such maps increases rapidly with expansion of the target environment. Here, we consider the problem of localization of a mobile robot based on existing 2D street maps. Although a large amount of research on this topic has been reported, the majority of the previous studies have focused on car-like vehicles that navigate on roadways; thus, the efficacy of such methods for sidewalks is not yet known. In this paper, we propose a novel localization approach that can be applied to sidewalks. Whereas roadways are typically marked, e.g. by white lines, sidewalks are not and, therefore, road boundary detection is not straightforward. Thus, obtaining exact correspondence between sensor data and a street map is complex. Our approach to overcoming this difficulty is to maximize the statistical dependence between the sensor data and the map, and localization is achieved through maximization of a mutual-information-based criterion. Our method employs a computationally efficient estimator of squared-loss mutual information, through which we achieve near real-time performance. The efficacy of our method is evaluated through localization experiments using real-world data-sets Graphical Abstract: